Implementasi Politik Perempuan di Kota Makassar - Ahmad Hening Silaban (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : Many women in Makassar entered into a political party, either as a member or director. When the 2009 legislative elections, many women who run as a candidate member of the legislative. However, the 2009 elections have not been able to produce a large amount of women to sit as a member of parliament of Makassar. From the 50 legislators of Makassar, only 7 of them are women. The condition occurs for at least two factors. First, the women themselves who do not have high interest to enter into practical politics. Many incoming the participation of weomen in political parties and forward as a candidate just because of family or friends, not because of the desire and consciousness itself. Second, external factors or existing systems. Opportunities for women it has been awarded with the enactment of Law No. 10 Year 2008 concerning the election of members of DPR, DPD, and DPRD which contains 30 per cent quota for women. But the political parties as the main actor did not want to give women the opportunity to volunteer. In the management of such party, very few women who hold strategic positions. Likewise, in the process of pen-candidate’s, women only exist in the third. The condition is aggravated by the Election Commission which still pass political parties nominated women less than 30 percent.Keywords: Political Women, Quotas 30 Percent, Political Party